A NEW CONCEPT OF THE JUNCTION NATURE OF THE CASPIAN SEA BASIN AND MUGODZHAR - Richter Ya.A. (My University, 2006)
A new version of the collision of mobile belt with suboceanic plate is discussed by the example of the relations between collision structures of the southern termination of Ural (Mugodzhar) and preorogenic structures of the Caspian Sea basin located in the inner angle of the East-European platform. Structural geological and geophysical data are given and analyzed. The suture character of Hercynian boundary structures is revealed in the junction zone of Mugodzhar and the Caspian Sea basin.
Keywords: SUBOCEANIC PLATE; MOBILE BELT; COLLISION; AND EDGE JUNCTION